Defining Eosinophil Function in Adiposity and Weight Loss. (22nd August 2018) - Knights, Alexander J.; Vohralik, Emily J.; Hoehn, Kyle L.; Crossley, Merlin; Quinlan, Kate G. R.
Abstract : Despite promising early work into the role of immune cells such as eosinophils in adipose tissue (AT) homeostasis, recent findings revealed that elevating the number of eosinophils in AT alone is insufficient for improving metabolic impairments in obese mice. Eosinophils are primarily recognized for their role in allergic immunity and defence against parasitic worms. They have also been detected in AT and appear to contribute to adipose homeostasis and drive energy expenditure, but the underlying mechanisms remain elusive. It has long been recognized that immune cells such as macrophages respond to external signals to regulate adipose homeostasis and energy balance, however, less is known about the relevance of eosinophil activity in AT. As the authors propose in this review, given recent debate over the relative importance of their tissue‐specific abundance, the stage is now set for exploring the functionality and activation states of AT eosinophils. Abstract : Adipose tissue eosinophils may be more important than previously appreciated in driving adipose homeostasis and energy expenditure. Functional characterization of adipose eosinophil signaling networks, activation states, and secreted factors (including "eosinokines") will help us to design better strategies for combatting obesity and other metabolic disorders.